Disrupting Intracellular Homeostasis by Copper‐Based Nanoinducer with Multiple Enzyme‐Mimicking Activities to Induce Disulfidptosis‐Enhanced Pyroptosis for Tumor Immunotherapy - Jin, Xiao‐Kang; Zhang, Shun‐Kang; Zhang, Shi‐Man; Liang, Jun‐Long; Yan, Xiao; Lin, Yan‐Tong; Meng, Ran; Xu, Zi‐Han; Liu, Chuan‐Jun; Zhang, Xian‐Zheng (Advanced materials (Weinheim), 2025)
Given the crucial role of abnormal homeostasis in tumor cells for maintaining their growth, it may be more efficient with less effort to develop anti‐tumor strategies that target multiple combined mechanisms by disrupting intracellular homeostasis. Here, a copper‐based nanoinducer (CGBH NNs) with multiple enzyme‐like activities is designed and constructed to induce disulfidptosis‐enhanced pyroptosis through disrupting multiple intracellular homeostasis for effective tumor immunotherapy. Within the tumor microenvironment (TME), CGBH NNs can disrupt intracellular glucose homeostasis and inhibit NADPH production, leading to accumulation of cystine, which further blocked the substrate and key enzyme for synthesizing glutathione. Subsequently, through cascade catalytic reactions involving enzyme activities (glutathione peroxidase‐like, glucose oxidase and peroxidase‐like activities), CGBH NNs can produce massive reactive oxygen species (ROS) and further disrupt intracellular redox homeostasis, resulting in the disulfidptosis‐enhanced pyroptosis. The tumor cells undergoing immunogenic pyroptosis can release various cytosolic contents and inflammatory factors, eliciting robust immune responses by facilitating immune cell infiltration, and reprogramming the immunosuppressive TME. After the combination with immune checkpoint blockade therapy, CGBH NNs can effectively suppress the tumor growth and prolong the survival time of tumor‐bearing mice. This work presents a novel paradigm to trigger disulfidptosis‐enhanced pyroptosis by destroying intracellular homeostasis for anti‐tumor immunotherapy. A copper‐based nanoinducer (CGBH NNs) aimed to disrupt intracellular metabolism and redox homeostasis for inducing tumor cells disulfidptosis‐enhanced immunogenic pyroptosis. The combination of these two cell death modes could promote the release of damage‐associated molecular patterns and inflammatory cytokines, reprogramming the immunosuppressive TME and enhancing immune cells infiltration. The evoked robust immune responses helped to suppress tumor progression.